The Phenomenon of Hate Speech and Disinformation on Social Media: A Criminal Law Approach in Tackling Digital Crime - Ro'is, Nur; Ogotan, Arianti A; Novianty, Rica Regina (Journal of Strafvordering Indonesian, 2025)
The rapid development of information technology, especially social media, has changed the way people interact and access information. However, this openness creates a digital paradox in the form of the spread of hate speech and disinformation that is difficult to control, potentially triggering social conflicts and political polarization, especially in Indonesia. Social media algorithms that amplify provocative content create an echo chamber that magnifies the risk of radicalization and manipulation of SARA's identity. This phenomenon threatens the quality of democracy and social cohesion, requiring a firm but proportionate response to criminal law. Law Number 19 of 2016 concerning Information and Electronic Transactions (ITE Law) plays an important role in handling digital crime, but its implementation faces obstacles of multi-interpretation norms and limited capacity of the apparatus. Repressive law enforcement has the potential to curb freedom of expression and cause injustice. Therefore, legal reforms are needed that clarify the definition of hate speech and disinformation, improve the digital literacy of the apparatus, and have independent oversight mechanisms. A comprehensive approach that combines legal, technological, and social aspects can create a healthy, democratic, and inclusive digital space, while protecting society from the negative impacts of hate speech and disinformation.